Influence and distribution of lead nitrate on growth and secondary metabolite accumulation in Withania somnifera (L.) Dunal in vitro shoots - Natarajan, Kanimozhi; Rangasamy, Kousalya; Santhanu, Krishnapriya; Vinod, Sangeetha; Senthil, Kalaiselvi (Journal of Phytology, 2023)
Withania somnifera is a medicinal ayurvedic plant native to India. Lead (Pb) is a toxic heavy metal which has no biological function in plants. The aim of the present study is to investigate the influence of heavy metal Pb on W. somnifera at cellular level under controlled conditions. The role of Pb on shoots of W. somnifera was determined in terms of biomass, secondary metabolite production (High Performance Thin Layer Chromatography) and phytochemical quantification. Influence and accumulation of Pb at the cellular level were recognized using UV visible spectroscopy, field emission scanning electron microscope and x-ray diffraction analysis. The current result showed that the concentration up to 2.4 mM Pb for 7 days of exposure showed higher biomass and withaferin A yield compared to control shoots. On the other hand, other secondary metabolites such as flavonoids, phytosterols and phenols levels were reduced compared to control shoots. In the morphological study, Pb concentration in the analysed sample was determined as 2%. The probability of the nanoparticle nature of the bioaccumulated lead also verified using spectroscopy and x-ray diffraction analysis. To date, we are the first to report on the influence of Pb on in vitro shoot cultures of W. somnifera.